NFTS - Laurence, Tiana; Kim, Seoyoung (--For dummies., 2022)
"At the intersection of blockchain technology, smart contracts, and the world of collectibles, you'll find NFTs--non-fungible tokens. These fascinating (and potentially lucrative) new digital assets promise to revolutionize how we buy, sell, and track property. In this book, you'll learn how you can get in the mix and start making your own digital commodity moves. Find out where to buy and sell NFTs, how they work, and how to build your own tokens. Don't wait a moment longer. Jump into the NFT arena now and hold on if you can!"--Provided by publisher.